Why Use the Radial Artery? The Saphenous Vein is the Second Graft of Choice for CABG in Brazil - Loesch,Andrzej (2019)
Abstract The saphenous vein (SV) is the most commonly used conduit for coronary artery bypass surgery (CABG) and the second conduit of choice in Brazil and many other countries. The radial artery (RA) is suggested, by some, to be superior to SV grafts, although its use in the USA declined over a 10 year period. The patency of SV grafts (SVG) is improved when the vein is harvested with minimal trauma using the no-touch (NT) technique. This improved performance is due to the preservation of the outer pedicle surrounding the SV and reduction in vascular damage that occurs when using conventional techniques (CT) of harvesting. While the patency of NT SVGs has been shown superior to the RA at 36 months in one study, data from the RADIAL trial suggests the RA to be the superior conduit. When additional data using NT SVG is included in this trial the difference in risk of graft occlusion between the RA and SV grafts dissipates with there no longer being a significant difference in patency between conduits. The importance of preserving SV structure and the impact of NT harvesting on conduit choice for CABG patients are discussed in this short review.